Early versus late discharge from the hospital for low-risk parturients after spontaneous vaginal deliveries at Moi Teaching and Referral Hospital, Eldoret, Kenya: A randomized controlled trial. (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: The length of hospital stay after delivery is a major contributor to preventing postpartumcomplications and improving maternal and neonatal outcomes. Globally, the length of hospital stay afterdelivery has been reducing in recent times. However, there is limited understanding of the safety,outcomes, and complications of early discharge compared with late discharge in low- and middle-incomesettings.Objectives: To evaluate the outcomes of early versus late discharge from the hospital for post-spontaneous vaginal delivery low-risk parturient and healthy neonates in Moi Teaching and ReferralHospital, Eldoret, Kenya.Methods: A randomized controlled trial study design was employed. 744 mother-child dyads wererecruited into this study within the first hour postdelivery and were randomized into two groups: theintervention arm was those discharged within 24 hours and the control arm was those discharged after24 hours or more. The study participants were followed up over three months with over-the-phoneinterviews. The primary outcome was maternal rehospitalization.Results: Between July 2022 and October 2022, 744 mother-baby dyads were recruited and 372 wererandomly assigned to the intervention arm, and 372 to the control arm. There were 23 mothers in theintervention arm and 22 in the control arm who were lost to follow-up and subsequently excluded fromthe analysis. Baseline characteristics were similar between the study groups. There were 17 (4.9%)maternal readmissions in the intervention arm and 10 (2.9%) in the control arm (RR 2% (95%CI:-1.1%,5.2%; p-value=0.167).Conclusion: Early discharge for low-risk mothers and healthy neonates is noninferior to late discharge,with similar effects on maternal outcomes, neonatal outcomes, and breastfeeding patterns.